(untitled) (Global Journal of Human-Social Science, 2017)
Analyzed in this study were the State of Texas Assessment of Academic Readiness STAAR Mathematics and Science raw scores for Grade 5 students to determine the degree to which gender and ethnic racial i e Asian Black Hispanic and White differences were present Four school years i e 2011-2012 through 2014-2015 of statewide data were analyzed For all tests statistically significant differences were present by gender and by ethnicity race Trivial effect sizes were present between boys and girls for each analysis However medium effect sizes were revealed with regard to the raw score differences by ethnicity race for the four years analyzed Every year Asian students had the highest average test score followed by White Hispanic and Black students respectively A stair-step achievement gap Carpenter Ramirez Seven 2006 was present in each school year analyzed